Implemantasi Case Based Reasoning (CBR) Untuk Pengembangan Sistem Pakar Diagnosa Penyakit Gigi - Rosmini Rosmini; Ummi Syafiqoh; Asmah Asmah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Dental disease is a condition that can interfere with the teeth in carrying out their functions properly. Dental disease in humans ranks first on the list of the top 10 diseases that most people complain about in Indonesia. Dental disease can affect anyone of any age and gender. Dental disease initially does not cause problems and if allowed to continue can become a big problem. Dental disease has almost similar symptoms, therefore an expert system application is needed that can help diagnose dental disease so that you can get the right treatment before the dental disease develops into a more serious disease. The Case Based Reasoning (CBR) method is a method for solving problems by remembering the same/similar (similar) events that have occurred in the past then using that knowledge/information to solve new problems or in other words solve problems by dealing with solutions. - solutions that have been used. The results of the CBR method test resulted in a diagnosis of dental and oral disease with a similarity rate of 82%. So this method can be used to diagnose dental disease experienced by patients, thereby helping specialist doctors make decisions in disease management.